The Origins of Money and the Development of the Modern Financial System - L. Randall Wray (Levy Economics Institute of Bard College, 1993)
The origins of money and banking are explained in nearly every introduction money and banking course, but Wray proposes an alternative approach that emerges from a comparative analysis of economic institutions. Orthodox theory suggests that barter replaced self-sufficiency and increased efficiency by fostering specialization- subsequently, establishing some object as a medium of exchange permits greater efficiency. In essence, the orthodox economist espouses the view that we operate in a free market economy in which "neutral money is used primarily to facilitate exchange of real goods, undertaken by self-interested maximizers for personal gain." Institutionalists reject this argument because it emerges from the perspective of a rational economic agent facing scarce resources and unlimited wants-thus, the focus is on choice. Wray states that economic analyses must incorporate interactions between humans and nature, and that the economy is a "component of the material life process of society." Hence, the conventionalists' focus on choice should instead be directed at production and distribution. The Wray thesis suggests that money is necessarily endogenously determined: Monetary economies have not, and cannot, operate with exogenous money supply can function with a commodity reserve system, such a system is subject to periodic debt deflations. In sum, the monetarist policy prescription would be counterproductive to systemic stability and would not yield greater control of the money supply.
Keywords: 330